Submicroscopic Plasmodium infection during pregnancy is associated with reduced antibody levels to tetanus toxoid (2019)
ABSTRACT: Submicroscopic Plasmodium infections in pregnancy are common in endemic areas, and it is important to understand the impact of these low-level infections. Asymptomatic, chronic infections are advantageous for parasite persistence, particularly in areas where the optimal eco-epidemiological conditions for parasite transmission fluctuate. In chronic infections, the persistence of the antigenic stimulus changes the expression of immune mediators and promotes constant immune regulation, including increases in regulatory T cell populations. These alterations of the immune system could compromise the response to routine vaccination. This study aimed to evaluate the effect of submicroscopic plasmodial infection with P. falciparum and P. vivax during pregnancy on the immune response to the tetanus toxoid vaccine in Colombian women. Expression of different cytokines and mediators of immune regulation and levels of anti-tetanus toxoid (TT) immunoglobulin (Ig)G were quantified in pregnant women with and without submicroscopic plasmodial infection. The anti-TT IgG levels were significantly lower in the infected group compared with the uninfected group. The expression of interferon (IFN)-γ, tumour necrosis factor (TNF) and forkhead box protein 3 (FoxP3) was significantly higher in the infected group, while the expression of cytotoxic T lymphocyte antigen 4 (CTLA-4) and transforming growth factor (TGF)-β was lower in the group of infected. In conclusion, submicroscopic Plasmodium infection altered the development of the immune response to the TT vaccine in Colombian pregnant women. The impact of Plasmodium infections on the immune regulatory pathways warrants further exploration.